PERAN WORLD WIDE FUND FOR NATURE (WWF) DALAM MENINGKATAKAN JUMLAH POPULASI BADAK RHINOCEROS UNICORNIS DI INDIA - Akbar Dwi Rizki; Yusnarida Eka Nizmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research discusses the role of the World Wild Fund for Nature in efforts to increase the population of the Indian Rhinoceros or Rhinoceros Unicornis in India. The significant decline in population that this rhino species had experienced until it was threatened with extinction due to various factors became a serious problem. WWF as one of the international organizations working in the field of nature conservation has made various efforts to preserve these endemic Indian animals. To answer the question, the writer will analyze documents from secondary data such as books, journals, news on newspapers, websites and other relevant data. The collected data will be processed using qualitative methods. This study uses the concept of INGO (International Non-Government Organization) as a theoretical basis and Pluralism as a perspective. The results of the study showed that there were conservation efforts carried out by WWF and collaboration with various parties, so that the population of the Indian Rhinoceros species showed a significant increase in numbers. Keywords: WWF, Population, Conservation, Indian Rhinoceros, Rhinoceros Unicornis.